Quality of Life in Men With Congenital Adrenal Hyperplasia Due to 21-Hydroxylase Deficiency - Verhees, Myrthe J. M.; Engels, Manon; Span, Paul N.; Sweep, Fred C. G. J.; van Herwaarden, Antonius E.; Falhammar, Henrik; Nordenström, Anna; Webb, Emma A.; Richter-Unruh, Annette; Bouvattier, Claire; Perrière, Aude Brac de la; Arlt, Wiebke; et al. (Frontiers in Endocrinology, 2021)
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21OHD) is a disorder of adrenal steroid biosynthesis, leading to hypocortisolism, hypoaldosteronism, and hyperandrogenism. Impaired quality of life (QoL) has been demonstrated in women with CAH, but data on men with CAH are scarce. We hypothesized that disease severity and poor treatment control are inversely associated with QoL. In this study, 109 men (16-68 years) with 21OHD were included. The WHOQOL-BREF questionnaire was used to measure self-reported QoL domain scores on a 0-100 scale, where higher scores reflect better QoL. QoL domain scores were compared to published data on healthy and chronically ill reference populations from France, Germany, the Netherlands, and the United Kingdom. Differences in QoL scores among groups of disease severity and treatment control were tested within the study population. Overall, the men with CAH in this study appeared to rate their QoL as good. Median domain scores were 78.6 (IQR: 67.9-85.7) for physical health, 79.2 (IQR: 66.7-87.5) for psychological health, 75.0 (IQR: 58.3-83.3) for social relationships, and 81.3 (IQR: 71.9-90.6) for environment. In general, these scores were similar to WHOQOL-BREF domain scores in healthy references and higher compared to chronically ill reference populations. The domain scores did not differ among genotype groups, but patients with undertreatment or increased 17-hydroxyprogestrone concentrations scored higher on several QoL domains (p<0.05). Patients treated with dexamethasone or prednisone scored higher on the physical health, psychological health, and social relationships domains, but not on the environmental domain. In conclusion, QoL domain scores appeared to be comparable to healthy reference populations and higher compared to patients with a chronic illness. QoL was not influenced by genotype, but undertreatment and use of dexamethasone or prednisone were associated with higher QoL.